Implications of CYP1B1 in the treatment and prognosis of breast cancer - Maria Carolina Stipp; Jeanine Marie Nardin; José Claudio Casali-da-Rocha; Sérgio Ioshii; Alexandra Acco (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Cytochrome P450 1B1 (CYP1B1) enzyme plays an important metabolic role, especially in the metabolism of xenobiotics, endogenous substances, and procarcinogens. It may be involved in tumor initiation and progression. High levels of CYP1B1 have been identified in aggressive breast cancer cell lineages. The aim of the present study was to identify the expression and role of this enzyme in progression, prognosis, and clinical features of breast cancer patients. Methods Microarray paraffin-embedded tumor samples from 166 women with breast cancer were analyzed by immunohistochemical for CYP1B1. Statistical analyses were performed to correlate CYP1B1 expression with various clinical parameters among breast cancer patients. Bioinformatic tools were used to determine differential CYP1B1 mRNA and protein expression from patients in databases compared with our cohort. Results The CYP1B1 enzyme was overexpressed in 75% of breast cancer tissues. This result remained consistent regardless of the treatment regimen. Furthermore, although it was not negatively associated with overall survival, its expression was notably higher in patients who died and in patients with ER- (estrogen receptor negative) and PR- (progesterone receptor negative) tumors and p53 (protein 53) mutation carriers. These findings align with the consulted databases, which indicated a relationship between CYP1B1 expression, tumor progression, and malignancy, suggesting its potential role as a biomarker for tumor aggressiveness. Conclusions In conclusion, CYP1B1 showed a positive correlation with breast cancer malignancy, tumor progression, and toxicity effects in breast cancer patients. These findings emphasize the importance of CYP1B1 as a potential treatment target and its significance in the clinical management of breast cancer.